Seasonal Dynamics of Epiphytic Microbial Communities on Marine Macrophyte Surfaces - Korlević, Marino; Markovski, Marsej; Zhao, Zihao; Herndl, Gerhard J.; Najdek, Mirjana (Frontiers in Microbiology, 2021)
Surfaces of marine macrophytes are inhabited by diverse microbial communities. Most studies focusing on epiphytic communities of macrophytes did not take into account temporal changes or applied low sampling frequency approaches. The seasonal dynamics of epiphytic microbial communities was determined in a meadow of Cymodocea nodosa invaded by Caulerpa cylindracea and in a monospecific settlement of Caulerpa cylindracea at monthly intervals. For comparison the ambient prokaryotic picoplankton community was also characterized. At the OTU level, the microbial community composition differed between the ambient water and the epiphytic communities exhibiting host-specificity. Also, successional changes were observed connected to the macrophyte growth cycle. Taxonomic analysis, however, showed similar high rank taxa (phyla and classes) in the ambient water and the epiphytic communities, with the exception of Desulfobacterota, which were only found on Caulerpa cylindracea. Cyanobacteria showed seasonal changes while other high rank taxa were present throughout the year. In months of high Cyanobacteria presence the majority of cyanobacterial sequences were classified as Pleurocapsa. Phylogenetic groups present throughout the year (e.g. Saprospiraceae, Rhodobacteraceae, members without known relatives within Gammaproteobacteria, Desulfatitalea and members without known relatives within Desulfocapsaceae) constituted most of the sequences, while less abundant taxa showed seasonal patterns connected to the macrophyte growth cycle. Taken together, epiphytic microbial communities of the seagrass Cymodocea nodosa and the macroalga Caulerpa cylindracea appear to be host-specific and contain taxa that undergo successional changes.